The Paths of Books of Latvian Jews during World War II - Dreimane, Jana (Knygotyra, 2018)
[full article, abstract in English; abstract in Lithuanian]The aim of the research is to find out the influence of the Nazi regime on preservation of historical book collections, which were established in Jewish societies, schools, religious organizations and private houses in Latvia until the first Soviet occupation (1940/1941). At the beginning, libraries of Jewish associations and other institutions were expropriated by the Soviet power, which started the elimination of Jewish books and periodicals published in the independent Republic of Latvia. The massive destruction of Jewish literature collections was carried out by Nazi occupation authorities (1941-1944/45), proclaiming Jews and Judaism as their main “enemies”. However, digitized archives of Nazi organizations (mainly documents of the Reichsleiter Rosenberg Taskforce) shows that a small part of the Latvian Jewish book collections was preserved for research purposes and after the Second World War scattered in different countries. Analysis of archival documents will clarify the Nazi strategy for Latvian Jewish book collections. It will be determined which book values survived the war and what their further fate in the second half of the 1940s was.
Keywords: Jewish libraries of Latvia, Nazi regime, The Reichsleiter Rosenberg Taskforce (Einsatzstab Reichleiter Rosenberg), Holocaust, displaced books